Revision of Trechus Clairville, 1806 of the Bale Mountains and adjacent volcanos, Ethiopia (Coleoptera, Carabidae, Trechini) - Schmidt, Joachim; Faille, Arnaud (European Journal of Taxonomy, 2018)
Based on a study of 2150 specimens of the genus Trechus Clairville, 1806 from the Bale Mts, Mount Chillalo, and Mount Enkuolo, southern Ethiopia, the current knowledge regarding systematics and distribution of the genus in the area is summarized. Twenty-six new species are described and figured in detail: Trechus abalkhasimi sp. nov. (southeastern slope of Bale Mts, below Mt Abalk-hasim); T. adaba sp. nov. (western Bale Mts, above Adaba); T. angavoensis sp. nov. (western Bale Mts, above Dodola); T. balesilvestris sp. nov. (western Bale Mts, above Adaba); T. bombi sp. nov. (southern escarpment of Bale Mts, Harenna Forest); T. colobus sp. nov. (western Bale Mts); T. depressipennis sp. nov. (northeastern margin of Sanetti Plateau, Bale Mts); T. dodola sp. nov. (western Bale Mts, above Dodola); T. fisehai sp. nov. (northern slope of Bale Mts, above Goba); T. grandipennis sp. nov. and T. hagenia sp. nov. (southern escarpment of Bale Mts, Harenna Forest); T. haggei sp. nov. (northeastern margin of Sanetti Plateau); T. harenna sp. nov. and T. harryi sp. nov. (southern escarpment of Bale Mts, Harenna Forest); T. iridescens sp. nov. (southeastern slope of Bale Mts, below Mt Abalk-hasim); T. mattisi sp. nov. (southern escarpment of Bale Mts, Harenna Forest); T. mekbibi sp. nov. (southern and western part of Bale Mts); T. minitrechus sp. nov. (northeastern slope of Mt Enkuolo); T. nanulus sp. nov. (southern escarpment of Bale Mts, Harenna Forest); T. nigrifemoralis sp. nov. and T. oppositus sp. nov. (western Bale Mts, above Dodola); T. rira sp. nov. (southern escarpment of Bale Mts, upper Rira Valley); T. sanettii sp. nov. (southeastern slope of Sanetti Plateau, Bale Mts); T. tragelaphus sp. nov. (western Bale Mts, above Dodola); T. transversicollis sp. nov. (southern escarpment of Bale Mts, Harenna Forest); T. wiersbowskyi sp. nov. (southern escarpment of Bale Mts, upper Rira Valley). New distributional data are provided for T. baleensis (Basilewsky, 1974), T. bastianinii Magrini & Sciaky, 2006, T. batuensis Magrini & Sciaky, 2006, T. chillalicus Jeannel, 1936, T. clarkeianus (Basilewsky, 1974), T. culminicola Jeannel, 1936, T. ericalis Magrini, Quéinnec & Vigna Taglianti, 2013, T. gallorites Jeannel, 1936, T. gypaeti Vigna Taglianti & Magrini, 2010, T. oromiensis Magrini, Quéinnec & Vigna Taglianti, 2012, T. relictus Magrini, Quéinnec & Vigna Taglianti, 2012 and T. rotundicollis (Basilewsky, 1974). Cothresia robini Basilewsky, 1974 is considered a junior synonym of T. chillalicus Jeannel, 1936. A key to all species known to occur in the Bale Mts and adjacent volcanos is presented.